2007
DOI: 10.1016/j.ejphar.2006.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin in microdialysate from the mediobasal hypothalamus increases after progesterone administration to estrogen primed macaques

Abstract: Estrogen and progesterone act on gene and protein expression in serotonin neurons in a manner that suggests serotonin neurotransmission should increase. However, measurement of extracellular serotonin in macaques was lacking. Elevated prolactin secretion can be an indicator of increased serotonergic function and prolactin is increased by combined estrogen and progesterone treatment. We examined extracellular serotonin by microdialysis in a well-characterized macaque model of steroid-induced prolactin secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Recently, feeding mechanisms have also been shown to involve the function of the ARCN. The serotonin content in the ARCN of macaques is altered by the administration of sex steroids [5] and the injection of serotonin agonists into the ARCN can affect feeding in female rats [29]. Although serotonergic inputs are important to the function of the ARCN, the present results, indicate that serotonin and the DR do not play a critical role in the expression of ER␣ in this nucleus, or in the VMN.…”
Section: Discussioncontrasting
confidence: 50%
“…Recently, feeding mechanisms have also been shown to involve the function of the ARCN. The serotonin content in the ARCN of macaques is altered by the administration of sex steroids [5] and the injection of serotonin agonists into the ARCN can affect feeding in female rats [29]. Although serotonergic inputs are important to the function of the ARCN, the present results, indicate that serotonin and the DR do not play a critical role in the expression of ER␣ in this nucleus, or in the VMN.…”
Section: Discussioncontrasting
confidence: 50%
“…The mechanism by which this occurs is This would require a nuclear or membrane receptor, but reports on this are inconsistent between species. This laboratory has shown that HT increases tryptophan hydroxylase production in the dorsal raphe nucleus Sanchez et al, 2005) and serotonin release in the hypothalamus (Centeno et al, 2007). Serotonin neurons express ERb and PR for mediation of the action of ovarian hormones (Bethea, 1993(Bethea, , 1994Gundlah et al, 2000Gundlah et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian hormone replacement to ovariectomized (Ovx) macaques changed the expression of serotonin related genes and proteins in a manner that would cause an increase in serotonin neurotransmission (Bethea, Lu, 2002, Centeno et al, 2007, Sanchez et al, 2005, Smith et al, 2004). In a similar macaque model, E increased serotonin in several compartments of the basal ganglia and in frontal and cingulate cortex, supporting the concept that E increased serotonin neurotransmission (Sanchez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%